Intestinal helminth parasites of the grey wolf (canis lupus l.) In Serbia - Ćirović, Duško; Pavlović, Ivan; Penezić, Aleksandra (Acta Veterinaria Hungarica, 2015)
The grey wolf (Canis lupus L.) is the most widespread large carnivore in Europe with large populations in the Eastern part of Europe and the Balkan Peninsula. In this study, a total of 102 wolves were examined for intestinal helminth parasites. The carcasses were collected within the Serbian part of the wolf's range during the period 2009-2014. Nine helminth species were found: one nematode, Toxocara canis (3.9%), one trematode, Alaria alata (1.0%), and seven cestodes, Taenia pisiformis (1.0%), T. hydatigena (9.8%), T. polyacantha (2.9%), T. taeniaeformis (2.0%), T. (syn. Multiceps) multiceps (3.9%), T. serialis (1.0%) and Mesocestoides litteratus (1.0%). Taenia (syn. Hydatigera) taeniaeformis has been registered for the first time in a wolf from Europe. An overall moderate prevalence (16.7%) of infected wolves was recorded. There was no statistically significant difference in prevalence between sexes. Of the years studied, the highest prevalence was found in 2014 (57.1%). The maximum number of helminth species per host specimen was four.